Rapid thermal annealing induced modification in structural and electronic structure properties of Ti0.95Co0.05O2−δ thin films. (November 2016) - Rodrigues, E.C.; Sharma, S.K.; de Menezes, A.S.; Chae, K.H.; Gautam, S.; Aljawf, Rezq Naji; Kumar, Shalendra
Graphical abstract: Highlights: Thin films of Ti0.95 Co0.05 O2−δ on (1 0 0) oriented silicon wafer was deposited successfully. Ti L 3, 2 -edge showed that Ti ions are in 4+ valence state in pristine as well as in annealed films. Co L 3, 2 edge NEXAFS spectra infer that Co ions are in +2 valence state in pristine and N2 annealed films. AFM micrographs revealed that grain size increases when the film annealed in O2 and N2 atmosphere. Abstract: Thin film of Ti0.95 Co0.05 O2-δ was deposited on Si (100) using PLD method and annealed in O2 and N2 environment. Raman spectra confirm that all the films have rutile structure. Surface morphology indicates that the surface roughness and grain size increase with annealing. The electronic structure studied by NEXAFS spectroscopy at O K, Ti L3, 2 and Co L3, 2 -edges revealed that peak intensities decrease significantly for the film annealed N2 environment. The ligand-field splitting estimated from the energy difference between the t2g and eg features in O K-edge spectra were 2.71 eV for as-deposited and O2 annealed film, whereas reduced more than double (∼1.32 eV) for the film annealed in N2 . Atomic multiplet calculations and experimentally observed NEXAFS spectra at Co L3, 2 -edge and Ti L3, 2 -edge confirm that Co present in 2+ and Ti in +4 valence state, whereas the multiplet structures of O2 annealed film looks similar to Co metal.